2018
DOI: 10.1590/0034-7167-2016-0561
|View full text |Cite
|
Sign up to set email alerts
|

Workload of nurses: observational study of indirect care activities/interventions

Abstract: Objective: Observe the workfl ow of nurses in hospitalization units identifying indirect care activities/interventions; measure the frequency and average time spent in performing them; and to verify the associations between average time of the activities interventions grouped into categories and per hospitalization unit. Method: Observational exploratory study using the timed technique. It was conducted in medical, surgical and specialized clinic units of a teaching hospital in the northwest of São Paulo Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 20 publications
1
23
0
9
Order By: Relevance
“…31 Nurses' workload entails the procedures carried out in the patient care and the time given for these procedures. 32 Nurses have a heavy workload because they attend to large number of patients and take responsibility for them. Their work overload prevents them from performing their tasks properly.…”
Section: Role-related Stressorsmentioning
confidence: 99%
“…31 Nurses' workload entails the procedures carried out in the patient care and the time given for these procedures. 32 Nurses have a heavy workload because they attend to large number of patients and take responsibility for them. Their work overload prevents them from performing their tasks properly.…”
Section: Role-related Stressorsmentioning
confidence: 99%
“…A range of studies have used objective measurements to describe nurse physical activity during work hours (Hajo et al., 2020; Reed, Prince, et al, 2018; Schall, Fethke, & Chen, 2016), in leisure time (Loef et al., 2018; Reed, Cole, et al, 2018), and specifically in ICU clinical settings (Kwiecień‐Jaguś, Mędrzycka‐Dąbrowska, Czyż‐Szypenbeil, Lewandowska, & Ozga, 2019). The measurements for identifying ICU nurse physical work activity have included time‐motion analysis utilising an e‐ICU technology (Tang, Mazabob, Weavind, Thomas, & Johnson, 2006), a video‐based method (Fiedler, Weir, van Wyk, & Andrews, 2012), time‐tracking software (called Togg; de Campos, de Oliveira, & Perroca, 2018), and pedometers (Kwiecień‐Jaguś et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cumulatively, this body of research has shown that ICU nurses spent the majority of their time in standing and walking behaviours while performing nursing tasks (de Campos et al., 2018; Fiedler et al., 2012; Tang et al., 2006). However, the study by Kwiecień‐Jaguś et al.…”
Section: Introductionmentioning
confidence: 99%
“…The interventions considered more representative differ from other studies and showed greater time-consuming values in: documentation (13)(14)(15)(16)(17) ; supervision (14)(15)(16) ; shift change (13)(14)(15)17) ; health care information exchange (13,(16)(17) ; and delegation (13)(14)(15) .…”
Section: Resultsmentioning
confidence: 91%